Low‐temperature tolerance in coprophagic beetle species (Coleoptera: Scarabaeidae): implications for ecological services. (1st June 2021) - Gotcha, Nonofo; Machekano, Honest; Cuthbert, Ross N.; Nyamukondiwa, Casper
Abstract : 1. Low temperatures affect insect functioning and population dynamics. Although temperate species cope with low temperatures better than their tropical counterparts, increasing temperature variability due to climate change exposes tropical species to frequent cold stress. For keystone insect species providing important ecosystem services, low‐temperature tolerances, and behavioural responses remain unknown, hampering predictions under climate change. 2. The present study examined low‐temperature physiology [critical thermal minima (CTmin ) and chill coma recovery time (CCRT)] of six dung beetle species across three activity times: diurnal Allogymnopleurus indigaceous (Reiche) and Euoniticellus intermedius (Reiche); crepuscular Onthophagus alexis (Klug) and Onthophagus gazella (Fabricius), and; nocturnal Copris elephenor (Klug) and Scarabaeus zambezianus (Peringuey). Further, ecological service delivery (dung removal) was examined between diurnal and nocturnal species across the temperature regimes. 3. Nocturnal species had significantly greater cold tolerance than both crepuscular and diurnal species, while CCRT was significantly shortest in diurnal than both crepuscular and nocturnal species. Dung ball production between diurnal and nocturnal species interacted with temperature, with diurnal species producing significantly fewer balls at low temperatures, while nocturnal beetles were not significantly affected. In turn, nocturnal species produced significantly larger balls than the diurnal species across temperatures. Effects of temperature regime shifts were intertwined with the foraging ecology of individual species. 4. Future research should quantify species' functional responses toward different amounts of dung masses as stressful temperatures increase. 5. Results are significant for determination of species thermal ranges and predicting costs of low‐temperature stress through reduced ecological services under shifting thermal environments. Abstract : Cold tolerance (CTmin and CCRT) were significantly influenced by beetle activity timing with night active species having higher cold tolerance (CTmin ) than both crepuscular and diurnal species Effects of temperature interacted with species in mediating dung removal services Low‐temperature stress may offset diurnal dung beetles' ecological services through reduction in dung removal Results predict species' thermal ranges and elucidate the ecological costs of low‐temperature stress under shifting thermal environments